Dual-Band and Dual-Polarization CPW Fed MIMO Antenna for Fifth-Generation Mobile Communications Technology at 28 and 38 GHz - Yi-Fan Tsao; Arpan Desai; Heng-Tung Hsu (IEEE Access, 2022)
In this paper, we developed a 2-port dual-band and dual-polarization multiple-input- multiple-output (MIMO) antenna for fifth-generation (5G) mobile applications at 28 and 38 GHz. The antenna was fabricated using a double-layer Rogers ™ RO4003 substrate with a footprint of $3.77\,\,λ _{0}× 1.86\,\,λ _{0}$ ( $λ _{0}$ being the free-space wavelength at 28 GHz). The aperture-coupled patch configuration fed by a coplanar waveguide (CPW) transmission line is adopted as the elementary antenna. The top patch and the coupling aperture are designed to radiate at 38 GHz and 28 GHz respectively for dual-band operation. Further enhancement of the directivity at 28 GHz is achieved through the top patch acting as a parasitic director. A 2-by-4 array antenna for MIMO application was then constructed through physical rotation of the single element at +45 and −45 degrees to create polarization diversities. The 2-port MIMO antenna realized using this configuration demonstrated an impedance bandwidth of S11<−10 dB covering 27.6–30.3 GHz and 33.4–40.4 GHz, a gain of greater than 8 dBi, isolation of more than 20 dB and a cross-polarization level of greater than 20 dB. The important MIMO parameters such as ECC, DG, TARC, and MEG have also been characterized and presented.